Centrality of Panchayati Raj in Water Conservation and Management - Nupur Tiwari, (Journal of Soil and Water Conservation, 2022)
The solution to the decline of water resources is today often addressed to the revival of community traditions and people’s participation in water management. The success of water management crucially entails working out collective protocols of equitable and sustainable use of surface and ground water, bringing together of scientists and farmers to evolve a dryland agriculture package and a host of other livelihood options, detailed land-use planning at the micro-watershed level and the mobilization of rural communities in the direction of the disadvantaged. However, any strategy for water conservation, management and utilization need a  community based and region specific strategy that is owned by the people who have to implement it. While democratic decentralization in the county has been exemplary, yet, the third tier of governance had not been as involved and effective in managing environmental resource as it ought to be. The result is overall deterioration and degradation of our natural resource base. In other words all environmental projects should involve the Panchayati Raj institutions since it is their mandate to protect and manage the natural resource base within their jurisdiction. The constitutional recognition that Panchayats enjoy, especially with regard to custodial rights over natural resources, definitively renders the most appropriate institution for local governance of natural resources. The inclusion of all residents of the villages within the fold of Panchayats makes them a far superior form of institution, despite all the limitations so we can say that effective environmental governance requires overall improvement in the quality of governance at the centre, state and local levels. Any single agency or for that matter government alone can not take various steps without active involvement of all the sections of society.